Hubungan Kadar HB dengan Perdarahan Postpartum di Rumah Sakit Umum Daerah Djasamen Saragih Tahun 2023 - Henni Jc Saragih; Sri Rezeki (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
According to the WHO (World Health Organization), every day in 2017 around 810 women died, at the end of the year reaching 295,000 people, of which 94% were in developing countries (WHO, 2019). The MDGs (Millennium Development Goals) which ended in 2015, were then continued with the development of the SDGs (Sustainability Development Goals) until 2030. The five biggest causes of maternal death in Indonesia in 2010-2016 were bleeding (30.3%), hypertension in pregnancy ( 27.1%), infection (7.3%), prolonged labor (1.8%), abortion (1.6%) and others (31.9%). This study aims to identify the relationship between HB levels and postpartum hemorrhage at the Djasamen Saragih Regional General Hospital in 2023.Type of quantitative research with a case control design. This study was conducted on a sample of 100 postpartum. To measure the characteristics of the respondents, a data collection form was used which was obtained through collecting data from the evaluation section at the Djasamen Saragih Regional General Hospital in 2023.Based on the statistical test using chi-square, the value of ρ = 0.001 (ρ <α, α = 0.05) is obtained, the strength of the relationship between the two variables is seen based on the contingency coefficient, which is 0.302, which means the strength of the relationship is moderate. Then the odds ratio (OR) results obtained OR = 0.215 [95% CI 0.087 – 0.532] which means that the range 0.087 – 0.532 does not exceed the value of 1, so postpartum mothers with low Hb levels during pregnancy have a greater chance of postpartum hemorrhage 0.215 than mothers postpartum Hb was normal during her pregnancy.There is a relationship between Hb levels and postpartum hemorrhage at the Djasamen Saragih Regional General Hospital in 2023